Understanding acute stress-mediated immunity in teleost fish - Guo, Huming; Dixon, Brian (Fish and shellfish immunology reports, 2021)
•Stress/immune interactions are conserved between teleosts and mammals.•In mammals chronic stress is immunosuppressive, acute stress can be immunoenhansive.•In teleosts chronic stress is immunosuppressive, but effects of acute stress are not clear.•Teleost acute stress has different effects than chronic stress but needs more study. The abilities and ways in which organisms respond to stress have long been demonstrated to affect the immune response of the organism. In mammalian studies, researchers have observed that chronic/long-term stress has a pronounced immunosuppressive effect, while studies in acute stress have demonstrated some immunoenhansive properties. These dynamics have been somewhat conserved in fish, as the effects of cortisol and chronic stress on the fish immune system are distinctly immunosuppressive, however, acute stress mediated immunomodulation is still poorly understood. This review explores the lesser studied non-cortisol stress hormones relevant to acute stress, and how they affect the immune response in Fish. Additionally, the effects of acute stress on various innate immune parameters and the regulation of immune related transcripts are discussed. Subsequently, this review attempts to establish the temporal transition between acute and chronic stress in the context of immune mediation. The conclusions of this review suggest that the modulating effects acute stress has on fish immunity is significantly different than that of chronic stress, yet more focused research must be conducted to further elucidate the mechanisms in greater detail.